Cyanuric Chloride as an Efficient Catalyst for the Synthesis of 2,3-Unsaturated O-Glycosides by Ferrier Rearrangement - Xiaojuan Yang; Na Li (The Scientific World Journal)
Cyanuric chloride has been found to be an efficient catalyst for the synthesis of 2,3-unsaturated O-glycosides from the reaction of 3,4,6-tri-O-acetyl-D-glucal and a wide range of alcohols in dichloromethane at room temperature. The experimental procedure is simple, and the products are obtained in high yields.